Diseño de un plan de negocio para la creación de una empresa dedicada a la fabricación de hamburguesa artesanal en la ciudad de Bogotá (2020)
The hamburger is a popular and known meal by the consumers around the world. It is a characteristic food since the 20th century, however, it was not always consumed as we know it today. It has had to go through many changes throughout history, it had different functions at each moment in the history of mankind, such as the times of war, the industrial revolutions, the dynamics changes of society, the globalization, among other factors that have influenced the preparation, appearance, ingredients and flavors; and that have made it come to the food we know today. This continuous reinvention has been adapted to each of the tastes through the different presentations. It is a fact that the hamburger has gained a prestige and has managed to be within the most relevant gastronomic trends, from fast food, to gourmet food.